Huperzia serrata Extract ‘NSP01’ With Neuroprotective Effects-Potential Synergies of Huperzine A and Polyphenols - Callizot, N.; Campanari, ML; Rouvière, L; Jacquemot, G; Henriques, A.; Garayev, E; Poindron, P. (Frontiers in Pharmacology, 2021)
Huperzia serrata (Thunb.) Trevis is widely used in traditional asiatic medicine to treat many central disorders including, schizophrenia, cognitive dysfunction, and dementia. The major alkaloid, Huperzine A (HA), of H. serrata is a well-known competitive reversible inhibitor of acetylcholine esterase (AChE) with neuroprotective effects. Inspired by the tradition, we developed a green one-step method using microwave assisted extraction in order to generate an extract of H. serrata, called NSP01. This green extract conserves original neuropharmacological activity and chemical profile of traditional extract. The neuroprotective activity of NSP01 is based on a precise combination of three major constituents: HA and 2 phenolic acids, caffeic acid (CA) and ferulic acid (FA). We show that CA and FA potentiate HA-mediated neuroprotective activity. Importantly, the combination of HA with CA and FA does not potentiate the AChE inhibitory property of HA which is responsible for its adverse side effects. Collectively, these experimental findings demonstrated that NSP01, is a very promising plant extract for the prevention of Alzheimer’s disease and memory deficits.